Using Response Cards Media to Improve the Students' Narrative Text Reading Skill of the Tenth Graders of MAN 1 Magelang in the School Year 2018/2019. - Sandi Dwi Nugroho (Faculty of Education and Teachers Training, 2019)
Reading is one of the important skills in English because by mastering reading students can get much information and knowledge. However, the tenth graders of MAN 1Magelang in the school year 2018/2019 still found difficulties in understanding reading English test of narrative text. It made their average score only 68.There are two main objectives of this research. First, it is to know the increase of the learning motivation in students’ narrative text reading skill of the tenth graders of MAN 1 Magelang in the school year 2018/2019. Second, it is to measure the improvement in students’ narrative text reading skill of the tenth graders of MAN 1 Magelang in the school year 2018/2019 who are taught using Response Cards media. The subject of this research was the tenth graders of MAN 1Magelang in the school year 2018/2019 of X IPS 7. The writer conducted a classroom action research that was divided into some cycles.As the results in Pre-Cycle, the students still had low learning motivation in the reading class. In Cycle I, many students were interested in using Response Cards media. In Cycle II, the students had better participation in teaching learning process.The writer concludes that the use of Response Cards media can increase the motivation in learning narrative text reading skill and there is a great improvement in students’ narrative text reading skill of the tenth graders of MAN 1 Magelang in the school year 2018/2019.